Hubungan Kejadian Bayi Berat Lahir Rendah dengan Riwayat Ibu Hamil Kekurangan Energi Kronis di Wilayah Puskesmas Pantoloan - Widya Pani (Poltekkes Kemenkes Palu, 2018)
One that affects fetal growth is the nutrition of pregnant women because during pregnancy the mother must meet the rapid growth needs of the fetus, and so that the output of the pregnancy is successful and perfect. But until now there are still many pregnant women who experience nutritional problems, especially malnutrition, such as Chronic Energy Deficiency (SEZ). The number of pregnant women experiencing SEZs in the Pantoloan Community Health Center Working Area in 2016 was a total of 67 pregnant women who delivered 8 LBWs. The purpose of this study was to determine the relationship of the incidence of low birth weight babies with a history of chronic energy-deficient pregnant women in the work area of Pantoloan Health Center. This research is an Analytical type with Cros Sectional research design with a population of 252 babies born in 2010 in the Work Area of Pantoloan Health Center. Sampling uses the Total Sampling technique. The criteria for the sample are taken if you have birth weight and maternal LILA data during pregnancy, if the data is incomplete, it is not sampled. Samples that meet the requirements are 52 babies. The results showed that pregnant women who experienced SEZ 32 people (61.5%), and LBW as many as 8 babies (15.4%). There was a significant relationship between the incidence of LBW and a history of SEZ pregnant women (p = 0.0017). The conclusion, that the better the nutritional status of pregnant women during pregnancy, the better the weight of the baby will be born. It is recommended for Pantoloan Health Center to improve health education programs about nutrition, and take LILA measurements regularly for pregnant women.